Sebaran Nematoda Sista Kentang di Wonosobo dan Banjarnegara, Jawa Tengah - Dani Sutanta Syafii; Lisnawita Lisnawita; Hasanudin Hasanudin (Jurnal Fitopatologi Indonesia, 2018)
Distribution of Potato Cyst Nematode in Wonosobo and Banjarnegara, Central JavaPotato cyst nematode (PCN), Globodera spp., is the primary pathogens that infect potato plants and has been distributed world wide. This study aimed to determine the geographic distribution and species of PCN that infect potato plants in Wonosobo and Banjarnegara, Central Java through a survey, morphological and molecular approaches. Morphological characters were observed among cyst (fenestra diameter, distance from anus to the fenestra, and the Graneks ratio, eggs (length and width of eggs), and the juvenile stage 2 (J2) (length and width of the body, the length and width of the head, the length of the stylet, knob type, as well as the length of the tail). While the molecular identification by polymerase chain reaction is based on the amplification of the internal area transcribed spacers using G. rostochiensis PITSr3 specific primer, G. pallida PITSp4 specific primer and universal nematode primer ITS5. Twelve isolates of PCN, i.e. 5 isolates from Wonosobo and 7 isolates from Banjarnegara were used in this study. The results showed that all isolates were identified as single species, G. rostochiensis.